Violence in African elections : between democracy and big man politics - Söderberg, Mimmi; Bjarnesen, Jesper (Africa now (Zed Books), 2018)
A comprehensive examination of the causes of Africa's violent electoral clashes, and the consequences for African democratization and peace-keeping.